2002
DOI: 10.1039/b209840g
|View full text |Cite
|
Sign up to set email alerts
|

The important effect of ligand architecture on the selectivity of metal ion recognition in An(iii)/Ln(iii) separation with N-donor extractants

Abstract: The existence of a strong correlation between ligand architecture and metal ion binding selectivity is demonstrated through large differences in the separation efficiencies found in the selective extraction of Am3+ from an acidic mixture of Am3+ and Eu3+ for three new tetrapodal hexadentate ligands containing four 2-pyrazinylmethyl groups attached to three different diamino spacers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 11 publications
1
40
0
Order By: Relevance
“…[3840, 83, 91116] While these complexes ranged in nuclearity, the majority were monomers adopting a 2IS/1OS arrangement [(L) x LnI 2 ](I)[38, 40, 9196, 106, 111, 117] (where L = neutral ligand or organic solvents such as: Pr i OH,[38] THF,[106, 117] and py[38, 106]) or the 3IS arrangement that utilizes combinations of bulky neutral ligands,[83, 95, 107, 110, 114, 118] THF,[98, 100, 102, 113] or Pr i OH [39] to fill the coordination sphere. However, no structure reports of the LaI 3 •MeOH derivatives have been previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…[3840, 83, 91116] While these complexes ranged in nuclearity, the majority were monomers adopting a 2IS/1OS arrangement [(L) x LnI 2 ](I)[38, 40, 9196, 106, 111, 117] (where L = neutral ligand or organic solvents such as: Pr i OH,[38] THF,[106, 117] and py[38, 106]) or the 3IS arrangement that utilizes combinations of bulky neutral ligands,[83, 95, 107, 110, 114, 118] THF,[98, 100, 102, 113] or Pr i OH [39] to fill the coordination sphere. However, no structure reports of the LaI 3 •MeOH derivatives have been previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…2) As a result, considerable efforts have been devoted to the development of new nitrogen-donor extractants for separating An(III) from Ln(III). 3) Jensen et al reported that N,N,N 0 ,N 0 -tetrakis(2-methylpyridyl)ethylenediamine (TPEN) demonstrates 100-fold preference for Am(III) over Ln(III) from the difference between stability constants with these metal ions in the aqueous phase. 4) TPEN is a hexadentate ligand which has six softdonor sites as a kind of podand type molecule and can encapsulate a metal ion.…”
Section: Introductionmentioning
confidence: 99%
“…[9] However, An/Ln separation can be more easily achieved by exploiting the slightly stronger interactions that An III present with the softer S-and N-containing ligands [1,3] of the SANEX processes. [10,11] Different pyridine derivatives, such as terpyridines and 2,6-bis(triazinyl)pyridines, [12][13][14][15][16] or dithiophosphinic acids [17][18][19] show quite remarkable separation factors. Among these ligands, N-alkylpicolinamides have also been proposed as ligands for the selective extraction of An from radioactive waste [2,20,21] as they show promising separation factors (S Am/Eu Ϸ 9) under optimum conditions.…”
Section: Introductionmentioning
confidence: 99%